Pengaruh Total Quality Management (Tqm) Dan Self Efficacy Terhadap Kinerja Karyawan Pt. Bakrie Sumatera Plantations Tbk Kisaran - Kartika Sahara; Febyo Angela (Edumaniora : Jurnal Pendidikan dan Humaniora, 2025)
The advancement of a company or organization is highly dependent on the quality of its human resources. The term "human resources" refers to the full potential possessed by each individual, enabling them to effectively navigate the increasingly competitive global landscape. Human resources with high skill levels and quality are considered valuable assets for organizations. The objective of this study is to determine the impact of Total Quality Management (TQM) and self-efficacy on employee performance at PT Bakrie Sumatra Plantations Tbk Kisaran. The research design is quantitative, employing an associative approach. The population under study consists of the workforce of PT Bakrie Sumatra Plantations Tbk Kisaran, with a sample size of 51 respondents. The sampling method used is probability sampling through simple random sampling. Primary data were collected through direct distribution of questionnaires, while secondary data were obtained through a literature study. The findings of this study indicate that Total Quality Management (TQM) has a significant positive effect on employee performance, as evidenced by a t-count value of 5.028, which is greater than 2.010, with a significance value of 0.000, which is less than 0.05, and a regression coefficient value of 0.693. Additionally, self-efficacy has a significant positive effect on employee performance, as indicated by a t-count value of 2.230, exceeding the threshold of 2.010, with a significance value of 0.030, and a regression coefficient value of 0.337. In simultaneous testing, the variables of Total Quality Management (TQM) and self-efficacy exert a combined effect, accounting for 43.7% of the total impact, while the remaining 56.3% is attributed to factors outside the scope of this study.